2022
DOI: 10.3389/fonc.2022.831355
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Serum Tumor Markers and Blood Inflammation Markers in Differentiating Pancreatic Serous Cystic Neoplasms and Pancreatic Mucinous Cystic Neoplasms

Abstract: Although many studies have emphasized the prognostic and diagnostic value of tumor markers and various inflammation-related markers, their clinical significance in differentiating benign and malignant pancreatic cystic neoplasms (PCNs) remains to be clarified. The present study explored the value of serum tumor markers and inflammation-related biomarkers in the differentiation of pancreatic serous cystic neoplasms (SCNs) and pancreatic mucinous cystic neoplasms (MCNs). A total of 79 patients with PCNs were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Using a combination of these factors of immune and nutritional status, a novel indicator, LA (Lymphocytes × albumin), caught our interest. The LA, calculated by the product of lymphocytes and albumin, was first proposed in distinguish benign and malignant pancreatic cystic neoplasm [ 17 ]. Recently, it had been demonstrated that low LA was particularly related to poor survival outcomes in rectal cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of these factors of immune and nutritional status, a novel indicator, LA (Lymphocytes × albumin), caught our interest. The LA, calculated by the product of lymphocytes and albumin, was first proposed in distinguish benign and malignant pancreatic cystic neoplasm [ 17 ]. Recently, it had been demonstrated that low LA was particularly related to poor survival outcomes in rectal cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article by Wang et al. ( 1 ) which identified the value of carbohydrate antigen 19-9 (CA19-9) and [lymphocyte × albumin (ALB), LA] in differentiating serous cystic neoplasms (SCNs) and mucinous cystic neoplasms (MCNs). We appreciated the great efforts that the authors made to help the management of pancreatic cystic neoplasms (PCNs).…”
mentioning
confidence: 99%